On the effect of investment disputes on bilateral portfolio investment in emerging markets - Jannik A. Nauerth (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2023)
This paper investigates the effect of arbitral proceedings on bilateral portfolio equity investments in emerging markets. Investment disputes may deter foreign investors as they reveal a government's poor behavior towards foreign investors. The analysis investigates the effects of the first initiation of arbitral proceedings, the first outcome in favor of the investor, and the first outcome in favor of the respondent state of arbitration proceedings. The database is an unbalanced panel of 55 home and 36 host countries from 2001 to 2018. Estimations do not reveal an unconditionally significant effect of arbitral proceedings on bilateral portfolio equity holdings. The impact becomes significant considering the interplay with bilateral investment treaties and political risk.
urn:nbn:de:bsz:14-qucosa2-884140
Keywords: F32; F53; G15; K33; 330; Investment disputes; Arbitration proceeding; Bilateral portfolio investment; Bilateral investment treaty; Investment protection; Emerging markets